Hi there!
L.H.S. = sin 2x + 2 sin 4x + sin 6x
= sin 2x + sin 6x + 2 sin 4x
= 2 sin
![\frac {2x + 6x}{2}](https://img.qammunity.org/2019/formulas/mathematics/college/f0dfg4ep5qwyl48d35fou08tub5rjficac.png)
. cos
![\frac {2x - 6x}{2}](https://img.qammunity.org/2019/formulas/mathematics/college/reyqq71h85syduc6vr6j1ttpje5gznfvvx.png)
+ 2 sin 4x
= 2 sin 4x . cos (-2x) + 2 sin 4x
= 2 sin 4x . cos 2x + 2 sin 4x
= 2 sin 4x (cos 2x + 1)
= 2 sin 4x (2 cos² x - 1 + 1)
= 2 sin 4x (2 cos² x) = 4 sin 4x . cos² x = R.H.S.
HENCE PROVED.
~ Hope it helps!